2012
DOI: 10.1038/ijir.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism and erectile dysfunction: a population-based case—control study

Abstract: Dysthyroidism has been highlighted as a common endocrine disorder associated with erectile dysfunction (ED); however, to date, no large-scale population-based study has investigated the association between hyperthyroidism and ED. This case--control study aimed to explore the association between ED and hyperthyroidism using a population-based data set. In total, 6310 adult patients who received new diagnoses of ED were recruited as cases together with 18 930 matched enrollees with no history of ED who served as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…27 A Taiwanese study by Keller .001) a significant association was observed. 33 In Corona et al's study of both EMAS and sexual medicine clinic populations discussed above, similar rates of overt primary hyperthyroidism in the men with sexual dysfunction and those in the general population were observed (0.2% vs 0.3%). In both populations, overt hyperthyroidism was strongly associated with ED (HR=14 EMAS, HR=16 sexual clinic, p<0.05 both).…”
Section: Hyperthyroidism In Menmentioning
confidence: 78%
“…27 A Taiwanese study by Keller .001) a significant association was observed. 33 In Corona et al's study of both EMAS and sexual medicine clinic populations discussed above, similar rates of overt primary hyperthyroidism in the men with sexual dysfunction and those in the general population were observed (0.2% vs 0.3%). In both populations, overt hyperthyroidism was strongly associated with ED (HR=14 EMAS, HR=16 sexual clinic, p<0.05 both).…”
Section: Hyperthyroidism In Menmentioning
confidence: 78%
“…These associations were confirmed in nested case-control analyses comparing subjects with overt hyperthyroidism with controls matched for age, body mass index, smoking status, and T levels. 56 Similarly, in a retrospective analysis of a health insurance database representative of Taiwan's general population, Keller et al 120 reported that subjects with ED were 1.64 times more likely to have been previously diagnosed with hyperthyroidism compared with control individuals without ED. TH-a and TH-b receptors were described in rat and human corpora cavernosa endothelial cells and SMCs.…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…Erectile function has a complex underlying mechanism affected by several factors. [1][2][3][4] Some recent studies have suggested that one of these factors may be estrogen levels. [5][6][7][8][9][10][11][12] For example, Baser et al 5 suggested that serum estrogen levels are correlated with symptoms of aging in men, and estrogen may therefore have an important role in these symptoms.…”
Section: Introductionmentioning
confidence: 99%